Estudo experimental da influência da mudança de direção na evolução do escoamento bifásico gás-líquido em golfadas - Barros, Hedilberto Antonio Albano (2019)
The gas-liquid two-phase slug flow pattern has as a main characteristic the gas and liquid phases intermittence passages and is found in oil and gas production and transportation lines, for example. The slug flow behavior knowledge is necessary for the correct pipes or equipment design, which operates on this flow pattern presence. In deep-water oil extraction operations, it is common to observe situations where the piping needs to adjust to the seabed relief, thus causing flow direction changes. Thus, in the present work, an experimental study of the gasliquid two-phase slug flow pattern in ducts with a slight direction change, consisting of horizontal initial sections followed by an inclined section is developed. The experimental measurements were performed in the NUEM-UTFPR experimental circuit, which is composed of a 35.6m long and 0.026m inner diameter pipe. The experimental circuit has resistive phase detection sensors installed in four (4) measuring stations and a high rate imaging camera that allows monitoring the following the slug flow characteristic parameters: the elongated bubble velocity, the piston, and elongated bubble lengths, the unit cell frequency and the void fraction. Three piping configurations were used, one completely horizontal, one upward and one downward with angles of ± 3º, ± 5º and ± 7º concerning the horizontal direction. Measurements were made for different air and water flow combinations at ambient temperature and outlet atmospheric pressure to ensure the slug flow pattern in the first measurement station. With the experimentally acquired data possession, the upward and downward changes influences in the slug flow were analyzed. In the upward cases, we observe the increases in the elongated bubble velocity and piston length, as well as the decreases in bubble length, especially for points with low gas and liquid flow rates (J=1-1,5m/s), where the bubble breaks in the elbow region. Regarding the descending cases, we observed the slug dissipation phenomenon that generates the stratified flow, a transition pattern between the slug and the stratified flows, and the gas piston in the region just after the elbow. It has been observed that in downward regions the elongated bubble velocity and piston length tend to decrease and in contrast, the bubble length tends to increase. The effects observed when there is a direction change are mainly caused by the buoyancy that exerts a force, sometimes in the same flow direction, or contrary, modifying the slug flow parameters.